Developmental regulation of tandem promoters for the major outer membrane protein gene of Chlamydia trachomatis. - Stephens, R S (1988)
Chlamydia trachomatis has a biphasic developmental cycle which is characterized by qualitative and quantitative changes in protein expression. The molecular mechanisms that mediate these changes are unknown. Evidence for transcriptional regulation of the chlamydial major outer membrane protein gene (omp1) was found by Northern hybridization of RNA isolated sequentially during the chlamydial developmental cycle. Early in the growth cycle a single transcript was detected, which was followed hours later in the cycle by an additional transcript. Mapping of the initiating nucleotide for each transcript suggested that this gene is regulated by differential transcription from tandem promoters.